Analisis Tingkat Risiko dan Strategi Pengendaliannya: Studi Kasus Seblak GSM - Rindu Aprillia; Asep Suwarna; Zahra Fauziahsari; Wulan Nur Aszad (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Micro, small, and medium enterprises (MSMEs) play an important role in the Indonesian economy, particularly in terms of employment and contribution to gross domestic product (GDP). One rapidly growing MSME sector is culinary, including seblak businesses, which are a specialty of the city of Bandung. This study aims to understand the concept of risk management and identify and analyze various risks faced by Seblak GSM MSMEs, both from operational, financial, market, human resources, and regulatory aspects, as well as formulate risk mitigation strategies that can be applied. This study uses a qualitative approach with direct observation and in-depth interviews with business owners. The results show that Seblak GSM MSMEs face risks related to raw materials, finance, operations, market, reputation, and human resources that can affect business continuity. Risk management is implemented through the stages of identification, analysis, evaluation, and mitigation, although it is still simple in nature. The SWOT analysis shows that the strengths of the business lie in its distinctive taste, affordable prices, and buffet concept, while its weaknesses and threats stem from competition and fluctuations in raw material prices. The conclusion of this study emphasizes that the implementation of systematic and sustainable risk management is very important for Seblak GSM MSMEs to improve business performance and maintain business sustainability amid sector dynamics.